A cell-free biosynthesis platform for modular construction of protein glycosylation pathways - Weston Kightlinger (Nature Portfolio, 2019)
Constructing biosynthetic pathways to study and engineer glycoprotein structures is difficult. Here, the authors use GlycoPRIME, a cell-free workflow for mixing-and-matching glycosylation enzymes, to evaluate 37 putative glycosylation pathways and discover routes to 18 new glycoprotein structures